2008
DOI: 10.1016/j.ejcts.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the mitral valve apparatus: evidence synthesis and critical reappraisal of surgical techniques

Abstract: Sub-valvular apparatus preservation after mitral valve replacement is not a new concept, yet to date there has been no quantification of its clinical effectiveness as a procedure and no consensus as to which surgical preservation technique should be adopted to achieve the best immediate and midterm clinical outcomes. This systematic review of current available literature aims to use an evidence synthesis and meta-analytic approach to compare outcomes following replacement of the mitral valve with (MVR-P) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 60 publications
3
58
0
2
Order By: Relevance
“…In fact, differing surgical approaches using right thoracotomy or minimally invasive approach for MVS have been shown to improve safety and efficacy endpoints [47]. MVR has been advocated over MVRP, but routine sparing of the sub-valvular apparatus has resulted in reproducible reductions in operative mortality after MVRP [48]. Many patient groups do not appear to benefit from MVR over MVRP, particularly patients with a greater burden of comorbidities [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, differing surgical approaches using right thoracotomy or minimally invasive approach for MVS have been shown to improve safety and efficacy endpoints [47]. MVR has been advocated over MVRP, but routine sparing of the sub-valvular apparatus has resulted in reproducible reductions in operative mortality after MVRP [48]. Many patient groups do not appear to benefit from MVR over MVRP, particularly patients with a greater burden of comorbidities [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…16,24 In an experimental study, Hansen and associates 25 proposed that the apparatus of the anterior leaf let is more important than that of the posterior leaf let; however, another experimental study found no substantial difference between anterior and posterior chordal-sparing techniques. 8 Athanasiou and coauthors 26 published a meta-analysis that compared the outcomes of MVR with and without subvalvular-apparatus preservation (1,603 patients and 1,330 patients, respectively). This analysis suggested that preservation is superior to nonpreservation in regard to the perioperative mortality rate and the 1-and 5-year survival rates; further, it found no significant difference, in any of the outcomes of interest, between bileaflet and posterior leaflet preservation groups.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Use of a preservation technique that is simple, reproducible, and appropriate for the patient's individual anatomy, pathologic condition, and LV function is paramount. 26 Therefore, patients with a severely diseased subvalvular apparatus could benefit from decalcification of valve tissue, 27,28 use of artificial chordae, 13 or PMR. Chordal-sparing MVR (by use of artificial chordate) can be performed regardless of the severity of the subvalvular disease; however, determination of the optimal length of the artificial chordae is an important aspect of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…This may eventually lead to arrhythmias such as atrial fibrillation, or heart failure, where the heart is unable to pump enough blood to meet the body's needs (12). Considering its many advantages such as subvalvular apparatus preservation, protection of left ventricular systolic function (13,14), and avoiding risks of thromboembolism and bleeding resulting from warfarin (15,16), MVP has been acknowledged to be superior to replacement (15,(17)(18)(19). Several cardiac centres in Asian countries have performed rMVP for decades (20), and have gained a considerable amount of experience (3,4).…”
Section: Discussionmentioning
confidence: 99%